Mixed teaching quality evaluation of organizational behavior course based on CIPP model - Zhang, Sujun; Bai, Lifen; Yang, Binbin (Frontiers in Education, 2025)
IntroductionThe implementation of blended learning helps overcome the limitations of traditional “chalk-and-talk” didactic teaching and unidirectional passive learning, demonstrating significant value in cultivating students’ problem-solving skills, critical thinking, and enhancing instructional quality. However, there remains a lack of systematic evaluation frameworks for assessing blended learning quality in discipline-specific courses (e.g., Organizational Behavior).MethodsThis study developed a blended teaching quality evaluation system based on the CIPP (Context, Input, Process, Product) model, comprising four first-level indicators (context evaluation, input evaluation, process evaluation, and product evaluation) and sixteen second-level indicators, along with defining a five-level course performance rating set S (very low, low, medium, high, very high). Using the organizational behavior course repository from a public university in Henan Province as the sample, empirical analysis was conducted employing the Analytic Hierarchy Process (AHP).ResultsEmpirical results indicate the course’s blended learning quality achieved an overall “High” rating. The AHP method not only effectively evaluates teaching quality but also identifies specific issues in teacher-student interactions through indicator analysis.DiscussionThe proposed CIPP-AHP integrated framework provides a practical diagnostic solution for blended learning quality (supported by 2023 data). Its indicator system and grading criteria are generalizable to similar courses, offering referential value for optimizing instructional design and teacher professional development.